Hadith #2492 - Sunan Abi Dawud - Hilal bin Maymun al-Jhny هلال بن ميمون الجهني; Marwan bin Mua'wiya al-Fazari مروان بن معاوية الفزاري; Muhammad bin Bkar bin al-Ryan محمد بن بكار بن الريان الهاشمي مولاهم (Sunan Abi Dawud)
Al-Rumaisa was the foster sister of Umm Sulaim.
Grade: Sahih